How does a licensing business manage its brand through third party B2B relationships - Kivimaa, Onni (2022)
Brand licensing in the consumer product market is an interesting topic yet there has not been much research done about it. As a business type it requires understanding of both B2B and B2C markets as it consists of both B2B relationships and relationships with the consumers. Relationship management and licensing as a general business type have been discussed in previous research, but it is a new thing to investigate a case company and their licensing relationships. The base of this study was rather simple: what are the main challenges of different priorities of the licensor and the licensees in licensing busi-ness and how could the relationships be developed? In the beginning the aim was to explain the licensing business type and its typical characteristics. The theoretical back-ground included relationship literature, branding literature, and licensing specific stud-ies. After this, seven interviewees were chosen including 4 Company X internals and 3 externals. The interviews were conducted with a semi-structured approach to get deep information from each individual. The study results were similar to some previous re-search findings, but this study combined that information in a meaningful way for the case organization: brand understanding and licensee’s opportunistic behavior are threats to the licensor. Relationship management is essential and honest and constant communication is required both internally and with partners to avoid surprises and create trust. Licensing partners should always be chosen with care, taking into account both their fit to the licensor’s brand, but also their competence and resources.